Backsliding to Autocracy: The Case of Turkey under Erdoğan - Elazazi, Yasmina Khaled (AUC Knowledge Fountain, 2021)
Democratic backsliding is a gradual process that results from changes in formal political institutions and informal political practices that significantly affect how citizens engage with the state. Even though such a phenomenon may occur in different types of democracies, there is always a threshold that determines whether the state will completely backslide to autocracy or conserve being a “minimal democracy”. For instance, a current model of democratic backsliding is Turkey; a state which has been experiencing a decline in basic civil liberties, political rights and freedoms. According to Freedom House, from 2002 to 2020, Turkey’s “political environment” has decreased from 23 to 31 (on a scale of 0 to 40, 40 being the worst); moreover, its “global freedom” has deteriorated to 32 (on a scale of 100, 100 being the worst), which labeled it “not free”, compared to being “partly free” in 2002. Indeed, the literature indicates that such decline mostly stemmed from Erdoğan’s personalization of institutions and control of the military’s political power after the attempted coup of July 2016. Nevertheless, when examining the literature on democratization, studies reveal that undermining the political influence of the military is crucial to consolidate democracy, yet in the Turkish case that did not happen. Accordingly, an emerging puzzle is: why does a regime continue to backslide from democracy despite de-politicizing its military? How do other personalized institutions, within a state, determine the outcome of democratic transitions? Looking at Turkey under Erdoğan and the AKP, this thesis aims to examine the causes of democratic backsliding in relation to the de-politicization of the military.